Beta-Amyloid Monoclonal Antibodies for Alzheimer’s Disease: Development and Challenges - Li, Yiyang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
As one of the most common diseases of the elderly, the detection and diagnosis of Alzheimer’s disease (AD) remain a challenge at the early stage. As the disease progresses, patients will suffer from memory and cognitive loss, which will impair their ability to live independently. The care required for these patients will be costly and time-consuming, placing a significant burden on both the family and society. At the same time, Alzheimer’s disease has a complex pathogenesis and there is still and there is an unmet need for drugs that can reverse the disease. The beta-amyloid (Aβ) proteins produced by improper cleavage of amyloid precursor proteins tend to aggregate into insoluble plaques in the brain. This study reviews the latest progress in the treatment of AD with Aβ monoclonal antibodies (mAbs). In recent years, aducanumab, lecanemab, donenamab have been successively approved. Besides, small molecule drugs also play an important role in AD treatment. Despite the inability to impede the progression of the disease, they are still irreplaceable and effective in relieving symptoms at this stage. In addition, as Aβ deposition begins decades before clinical symptoms appear, advances in diagnostic technology are essential for early intervention. Future research needs to pay more attention to the side effects of this therapy and their solutions.